Molecular and Crystal Structure, Spectroscopy, and Photochemistry of a Dispiro Compound Bearing the Tetraoxane Pharmacophore - Amado, Patricia S. M.; Lopes, Susy; Bras, Elisa M.; Paixao, Jose A.; Takano, Ma-aya; Abe, Manabu; FAUSTO, RUI; Cristiano, Maria L. S. (Wiley-VCH Verlag GmbH, 2023)
The molecular structure and photochemistry of dispiro[cyclohexane-1,3 & PRIME;-[1,2,4,5]tetraoxane-6 & PRIME;,2 & PRIME;& PRIME;-tricyclo[3.3.1.1(3,7)]decan]-4-one (TX), an antiparasitic 1,2,4,5-tetraoxane was investigated using matrix isolation IR and EPR spectroscopies, together with quantum chemical calculations undertaken at the DFT(B3LYP)/6-311++G(3df,3pd) level of theory, with and without Grimme's dispersion correction. Photolysis of the matrix-isolated TX, induced by in situ broadband (& lambda;>235 nm) or narrowband (& lambda; in the range 220-263 nm) irradiation, led to new bands in the infrared spectrum that could be ascribed to two distinct photoproducts, oxepane-2,5-dione, and 4-oxohomoadamantan-5-one. Our studies show that these photoproducts result from initial photoinduced cleavage of an O-O bond, with the formation of an oxygen-centered diradical that regioselectivity rearranges to a more stable (secondary carbon-centered)/(oxygen-centered) diradical, yielding the final products. Formation of the diradical species was confirmed by EPR measurements, upon photolysis of the compound at & lambda;=266 nm, in acetonitrile ice (T=10-80 K). Single-crystal X-ray diffraction (XRD) studies demonstrated that the TX molecule adopts nearly the same conformation in the crystal and matrix-isolation conditions, revealing that the intermolecular interactions in the TX crystal are weak. This result is in keeping with observed similarities between the infrared spectrum of the crystalline material and that of matrix-isolated TX. The detailed structural, vibrational, and photochemical data reported here appear relevant to the practical uses of TX in medicinal chemistry, considering its efficient and broad parasiticidal properties.
Keywords: DFT Calculations; IR and EPR; X-ray Diffraction